Effect of Lignite Composition on Mercury Removal from Flue Gas in Sulfide Forced Wet Flue Gas Desulfurization (WFGD) Installations—Full-Scale Experiments - Dariusz Łuszkiewicz; Maria Jędrusik; Arkadiusz Świerczok; Mariola Kobylańska-Pawlisz; Karel Borovec; Lukas Pilar (Energies)
In this article, the results of full-scale experiments on the addition of a sodium sulfide to the <semantics>CaCO3</semantics> slurry circuit in a wet flue gas desulfurization (WFGD) plant are presented. Tests are performed on two comparable WFGD installations (spray tower, 4 spraying levels and two stage gypsum de-watering by hydrocyclones and vacuum belt filter) which allows the investigation of the influence of lignite composition (lignite mined in Poland and the Czech Republic are compared) on the reduction in mercury emission. Additionally, the efficiency of precipitation of metals from the slurry (Hg, Zn, Pb, Cd, Cr, Cu, Ni, Fe, Se, and Mn) is investigated as the result of sulfide addition. For both objects, mercury re-emission from absorber occurs (the concentration of mercury in the chimney is higher than that before the WFGD absorber) and the sulfide addition to WFGD slurry stops this phenomenon. The addition of sulfide works effectively (mercury removal efficiency from flue gas reaches up to 88% for Polish tests and up to 87% for Czech Republic tests). For the tests in the Poland power plant, all of measured metals are precipitated from the slurry (precipitation of metals efficiency varied from 2% for zinc to 88% for mercury), but in the case of the test in the power plant in the Czech Republic, there is no effect on manganese, iron, and lead (precipitation of metals efficiency varied from 6.5% for copper to 86% for mercury). The addition of sulfide works effectively for lignite mined in Polish and Czech power plants under the conditions of similar WFGD installations.